2005
DOI: 10.1891/0739-6686.23.1.245
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Use, Misuse, Abuse, and Dependence in Later Adulthood

Abstract: Considerable research has focused on alcohol problems in older adults, but the clinical utilization of this knowledge has lagged at least 3 decades behind the scientific developments. This unfortunate situation takes on added significance as the “baby boomer” generation ages because more of them drink more often in larger quantities than previous generations. This chapter focuses more on the ramifications of use, misuse, and abuse than on chronic dependence because the prevalence in the former categories far o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…Firstly, the self-report of alcohol use should be interpreted with caution; it is possible that respondents underreported alcohol use, especially females. A number of risk factors associated with alcohol misuse or abuse in older adults reported in other studies (such as medication intake which may interact negatively with alcohol and religious involvement 3,4,8,13,14,17 ), were not assessed and should be assessed in future studies. For co-morbidities, given the limitations of self-reported morbidity, symptom questions and a related diagnostic algorithm were used to ascertain possible presence of co-morbidity conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, the self-report of alcohol use should be interpreted with caution; it is possible that respondents underreported alcohol use, especially females. A number of risk factors associated with alcohol misuse or abuse in older adults reported in other studies (such as medication intake which may interact negatively with alcohol and religious involvement 3,4,8,13,14,17 ), were not assessed and should be assessed in future studies. For co-morbidities, given the limitations of self-reported morbidity, symptom questions and a related diagnostic algorithm were used to ascertain possible presence of co-morbidity conditions.…”
Section: Discussionmentioning
confidence: 99%
“…1 Alcohol abuse poses special risks for increased morbidity and mortality among older adults 2 including increased risks for accidents and injuries, hypertension, cardiac dysrhythmic events, cancers, gastrointestinal problems, liver disease, neurocognitive deficits, bone loss and depression. [3][4][5] Many older adults take medications that may interact negatively with alcohol. 6 Alcohol use data of older adults from high income countries indicates that: in Japan, 47.9% of men and 10.1% of women drank alcohol almost daily 7 ; in the USA, 9% of elderly Medicare beneficiaries reported unhealthy drinking, with higher prevalence in men (16%) than women (4%) 8 ; and also in the USA, Schultz et al 9 reported that about 15% of older persons in a rural state were at risk for alcoholism.…”
Section: Introductionmentioning
confidence: 99%
“…55,56 At-risk drinkers may not have an alcohol disorder; however, heavy drinking episodes may be responsible for injuries and poor chronic disease outcomes. 22,58,59 The patient-centered medical home model of care being diffused nationally promises comprehensive, whole-person care that is facilitated and supported by electronic medical records. Alcohol screening with embedded counseling scripts in medical visit templates should be a component of such care, with the identification of and referral to appropriate resources as needed.…”
Section: Discussionmentioning
confidence: 99%
“…As adherence to treatment plans and self-management skills are essential to optimal chronic care management, alcohol consumption must be assessed and addressed. In light of the aging of the baby boomer generation, known to have higher alcohol consumption, 59 this call to action is timely and important.…”
Section: Discussionmentioning
confidence: 99%
“…In the few studies that investigate gender differences in alcohol abuse, a consistent finding is that women have lower levels of consumption, are less likely to meet the criteria for alcohol abuse or dependence, and are more likely to abstain altogether (Chermack, Blow, Hill, & Mudd, 1996;Stevenson, 2005). A study of alcohol consumption, rather than incidence of abuse or dependence, among residents of San Diego County aged 65 and older, found that whites were more likely to use alcohol than African-American or Mexican-American respondents (Molgaard, Nakamura, Stanford, Peddecord, & Morton, 1990).…”
Section: Demographics/prevalence Of Substance Abuse Disorders Among Omentioning
confidence: 99%